Tinjauan Hukum Ekonomi Syariah Tentang Jual Beli Online dengan Metode Dropship di Aplikasi Tokopedia - Syaripudin, Enceng Iip; Fathonih, Ah.; Quroni, Aqfa Fikril (STAI Al-Musaddadiyah Garut, 2025)
In Indonesia, the dropshipping sales system is growing rapidly. Dropshipping is a method where the seller (dropshipper) markets and sells products owned by another party without needing to stock the items. The dropshipper acts as a mediator between producers or suppliers, such as importers, and consumers. This study employs a descriptive qualitative method to depict the observed phenomena. Data were collected from verbal and written descriptions relevant to dropshipping practices. The findings reveal that the dropshipping mechanism is quite complex, with the potential for gharar elements between buyers and dropshippers. The contract used is an akad salam, where the buyer pays the dropshipper in advance, and the dropshipper then orders the item according to the buyer's request from the supplier. This system is permitted under Sharia law as long as the product specifications are clear and remain unchanged between the supplier and the dropshipper. For instance, dropshipping practices on the Tokopedia platform are considered not to affect the validity of the ba'i salam contract, provided that product specifications are transparent and understood by buyers. Keywords: Islamic Law; Buying and Selling Online ; Dropship; Tokopedia Application;